El buen danzante de tijeras recoge agua con una canasta - Montoya Rojas, Rodrigo (2007)
The author studies the scissors dancers 01 Huancavelica, Peru. Associating fieldwork and the review 01 16'/J Century documents, Rodrigo Montoya seeks lo specify (he relation between vitality and depletion in the past and present of the dance, the links between witchcraft and dance, among gods and devils. The materials gathered in his previous works in other cities and Andean villages and the interviews 01direct actors allow him to think over and to postu/ate a set 01 propositions on the interrelationships between society, music, dances and catholic festivities from the perspective 0f historical Anthropology.